English Language Pedagogical Approaches and Students’ Perceptions of their Reading, Writing, and Speaking Skills - Longay, Jasper (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined the relationship between English language pedagogical approaches and college students’ perceptions of their reading, writing, and speaking skills. Anchored on Paul Nation’s Four Strands Framework, Explicit Instruction Theory, and Blended Learning Theory, the study focused on Communicative Language Teaching, Task-Based Language Teaching, and the Grammar-Translation Method as instructional approaches in English language education. A quantitative descriptive-correlational research design was used, involving 172 college students from selected private higher education institutions in Davao City who were enrolled in general English courses during academic years 2025 and 2026. Data were gathered using a two-section survey questionnaire adapted from established language pedagogy and proficiency scales, with acceptable reliability. Mean, standard deviation, Pearson correlation, and multiple linear regression were used for data analysis. Findings showed that Communicative Language Teaching, Task-Based Language Teaching, and the Grammar-Translation Method were implemented extensively. Students also reported extensive perceived proficiency in speaking, reading, and writing. A significant positive relationship was found between English language pedagogical approaches and students’ perceptions of their language skills. Regression results further showed that the combined pedagogical approaches significantly predicted students’ perceptions, with Task-Based Language Teaching emerging as the only significant predictor. The study concluded that task-oriented, collaborative, and meaningful language activities play an important role in enhancing students’ perceived English proficiency. It recommended the continued integration of communicative, task-based, and grammar-focused instruction, supported by teacher training, curriculum enhancement, instructional resources, and student practice. The study aligns mainly with SDG 4, Quality Education, and secondarily with SDG 8, Decent Work and Economic Growth, by supporting language competence, academic success, and professional readiness. Its sustainability impact lies in strengthening educational, institutional, socio-economic, cultural, and technological sustainability through improved English language instruction.